V.I. VERNADSKY AND KYIV UNIVERSITY - Pavlyshyn, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Article is devoted to the 150th anniversary of the outstanding scholar-mineralogist, naturalist and science manager Academician V.I. Vernadsky. Highlights the diverse scientific and organizational activities V.I. Vernadsky in Kiev and Kiev University (1918–1919), is aimed at the creation of the Ukrainian Academy of Sciences and develop the scientific foundations of geochemistry and biogeochemistry.